Adherence to Therapeutic Regimen among Patients with Chronic Obstructive Pulmonary Disease Attending at Medical OPD of BPKIHS - Karki, Reena (Journal of Biratnagar Nursing Campus, 2023)
Background Chronic obstructive pulmonary disease (COPD) is a major health issue, associated with mortality and morbidities. The effective treatment of COPD requires long-term adherence to a therapeutic regimen. The objectives of this study were to assess the adherence to therapeutic regimens among patients with COPD and to find out the association of medication adherence with different factors.Methods The study used a descriptive cross-sectional research design. A total, 91 samples were chosen using a convenience sample method. An interview questionnaire was used for data collection. SPSS version 20 was used for data analysis. The level of confidence was set at 0.05.Results A high adherence rate was found in 60.4%. A significant association was found between mean adherence score with occupation, income to run family, opinion regarding the use of an inhaler, satisfaction with the time given by the physician during follow-up, presence of co-morbidity, interference in daily activities by the effect of medicine, perception about the need of medicine, presence of co-morbidity, family support in the treatment, stressful situation in the family affecting medication taking habit, stigmatization due to illness, support by social insurance, disease curability and feeling of susceptibility to illness or its complications. The study found a significant correlation between the mean adherence score and the frequency of total drugs (r= -0.221).Conclusion The finding of the study concluded that nearly two-thirds of the subjects had a high adherence rate to therapeutic regimens.